Exploring how to teach English as a Foreign Language in First Grade - Carvajal Téllez , Angélica María; Sánchez Correa, Nidia Adalia; Alarcón Cortés , Sharith Yaretsi; Bautista Estupiñan , Dherly Fernanda (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This research is the result of a study aimed to compare the teaching and learning of English as a foreign language in first grade at two primary schools located in Chiquinquirá – Boyacá. This was done through documentary revision, observation, semi structured interview to in-service teachers, teaching journals and artifacts produced during the pedagogical Strategy using TBL (Task based learning). The observation and the implementation of lessons allow comparing the teaching and learning in first grade, as well as to bring pedagogical recommendations for in-service teachers and the improvement of planning in both institutions. Although, the configuration of a case allows analyzing the role that teachers in training must play in their pedagogical practicum. The syllabus of Complementary training program is fed by the reflections taken from the process. The analysis with grounded theory allows to establish the categories: teacher training as main axis of English teaching, adaptation of materials to the classroom and tasks as meaningful learning. Finally, the active participation of teachers in training and in service teacher in the research mentorship of English engage the development of the abilities of synthesizes, compares and analyzes as high thinking skills.